Major Selection among Saudi Male University Students: a Multinomial Logit Model - Jiang, Guoping (International Journal of Criminology and Sociology, 2015)
Major selection is an important decision faced by all university freshmen. The topic has been studied thoroughly in individualistic cultures, particularly the US and Europe. The topic has not been as intensely investigated in the Middle East, an area influenced heavily by Islamic collectivist culture. Because of digital media and globalization, the Middle East is shifting toward individualism. Given this, we used a sample of male students at a science and engineering university to explore mechanisms that drive major selection in Saudi Arabia. A multinomial logistic analysis shows that family and high school teachers are important factors in their decision making process. Ease of study is also a factor considered when choosing a major.